PUTUSAN TINDAK PIDANA NARKOTIKA YANG DIPUTUS DILUAR DARI DAKWAAN PENUNTUT UMUM : Drug Offences Decided Outside Of The Public Prosecutor'S Indictment - Jihan Sukmawati Daratu; Abdul Ficar Hadjar (Faculty of Law, Universitas Trisakti, 2024)
In rendering a verdict, a judge is restricted from imposing a punishment if the criminal act is not specified in the charges filed by the public prosecutor. However, in narcotics cases, judges often decide to use articles not listed in the indictment, citing SEMA No 3/2015 as justification. The problem in the case of narcotics, specifically Number 7692 K Pid.Sus/2022, is whether the judge's decision to penalize the defendant with an uncharged article aligns with legal regulations. Additionally, it questions if the legal consequences of the imposed criminal sanctions deviate from the public prosecutor's indictment in the narcotics offense. To address these issues, the research method employed is normative legal research, using secondary data from primary and secondary legal materials, with a descriptive-analytical approach and deductive conclusions. The research findings reveal that the judge deems the defendant not a drug abuser due to a relatively small quantity of narcotics found. However, the judge overlooks the fact that the defendant engaged in transactions with several individuals, suggesting that the public prosecutor's article should have been applicable. In conclusion, the verdict beyond the indictment should be legally null, releasing the defendant from all legal claims.